Menguatnya Ikatan Patronase dalam Perpolitikan Indonesia - Fadiyah, Dina; Zakiyah, Ummi (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
This paper intends to see how the strengthening of patronage ties in Indonesian politics today is strengthened. The political euphoria in Indonesia is increasingly interesting, the article of political essence that occurs is not only about pure politics, but has been contaminated with various elements and interests. This is what makes the political elite must have a precise strategy to strengthen their position. This paper uses qualitative methods, descriptive and found that the strengthening of patronage ties in Indonesian politics is caused by mutual need or mutualism symbiosis between political elites and various elements such as community organizations for example.